A farmer's view on the current environmental conversation - Adams, M.H. (Journal of New Zealand Grasslands, 2016)
The brief for this paper was: "A farmer's view on protecting the soil, water and environment." However, I have headed in a slightly different direction and would like to focus on some of the tensions that exist within this brief. To help me do this, I will tell my family story starting with my grandfather James Adams. He sold both his 100 ha farm and agricultural contracting business in Duntroon, North Otago, to purchase an 890 ha farm in the Fairlie basin. In September 1950, at 42 years of age, my grandfather with his wife and eight children made the move north. Over the next 33 years he was able to acquire the neighbouring farms, effectively doubling the land area before two of his sons joined the business. Like many men from an era that included two world wars and a severe depression, James was a conservative man. He was prepared to borrow money to buy land, but not to develop it. Development had to be done out of income.